POPULASI SERANGGA Elaeidobius kamerunicus Faust BERDASARKAN TINGKAT KEMEKARAN (ANTHESIS) BUNGA JANTAN KELAPA SAWIT (Elaeis guineensis Jacq.). - Fauzi Abdullah Nasution; Ahmad Saleh; Wagino Wagino (Jurnal Agro Estate, 2017)
An of Elaeidobius kamerunicus urevil can be trusted to increase percentage of fruit set oil palm up to 75%. The activity of E. kamerunicus often in anthesis male ﬂower. The development of male ﬂower was growing in spikelet in a few days. Based on this matter needed observation about the population of E. kamerunicus in every ﬂorescence period in male unﬂoresectial of oil palm (Elaeis guineensis Jacq.). This observation was done in the year of planting at 2010 oil palm plantation in Sekolah Tinggi Ilmu Pertanian Agrobisnis Perkebunan (STIPAP), from March - June 2017. The methods used direct observation about growing ﬂower in spikelet of male ﬂower for four repetitions and data collection from calculating of E. kamerunicus population at 07.00 – 09.00 am and 10.00 – 12.00 pm with every times observation do for two repetitions in spikelet of male ﬂowers. The result of observation shows that the grow of male ﬂower going on for ﬁve days, start from 10,6%, 30,3%, 76,4%, 93,5%, and 100% ﬂowers grow in last day.The most population of E. kamerunicus in days i.e 4509 veewil/ inﬂoresencen.